Conhecendo a moeda brasileira - Colosso, Cristiane Otília; Silva , Elaine Maria Ultramare Ribeiro; Lima, Eliene Xavier de; Bento , Miriam Furtado; Schiavinato , Ricardo Leandro (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf